The chemistry of 700 years of precipitation at Dye 3, Greenland - Cragin, James H.; Langway, Chester C., 1929-, joint author.; Herron, M, joint author. (Hanover, N.H. : Corps of Engineers, U.S. Army Cold Regions Research and Engineering Laboratory, 1975)
Mode of access: Internet.